Simultaneous Dual Echo Gadolinium Enhanced MR-PET for Evaluation of PET Tracer Delivery in Altered Pathophysiology - Cowin, Gary J; Mardon, Karine; Houston, Zachary H.; Bhalla, Rajiv; Stimson, Damion H. R.; Thurecht, Kristofer J.; Brereton, Ian M. (Frontiers in Physics, 2022)
Efficacy of diagnostics and therapeutics for brain tumours can be modulated by vascular delivery and blood brain barrier permeability. Simultaneous dynamic gadolinium MR-PET enables independent assessment of vascular delivery and blood brain barrier integrity in a brain tumour animal model in the presence of a PET tracer. Dual echo dynamic gadolinium enhanced gradient echo imaging allows simultaneous calculation of T2* and T1 images from the TE image pairs. Relaxivity values then enabled determination of independent T2*- and T1-derived gadolinium concentrations simultaneously with measurement of [18F]DPA-714 radiotracer delivery. Separate T2*- and T1-derived gadolinium concentrations curves were derived in a selection of tumours and normal tissue, reflecting vascular delivery and tissue uptake. Changes in the PET activity curves were seen in tumours. The dramatic changes in the MR-derived vascular delivery and tissue uptake estimates, may improve the understanding of the alteration of delivery and uptake of new theranostic agents.